Pediatric Primary Care Telemedicine: Perspectives from English- and Spanish-Speaking Medicaid Enrollees - Anne R. Links; Eliana M. Perrin; Sarah Polk; Divya Konduru; Shafkat Meraj; Nakiya N. Showell; Suzanne M. Grieb; Helen Hughes (Telemedicine Reports)
Objective: To qualitatively explore Medicaid-enrolled parents’ and young adult patients’ perspectives and experiences with telemedicine in pediatric primary care. Methods: We conducted semi-structured interviews with participants to explore their experiences with telemedicine. Participants consisted of English- and Spanish-speaking parents and young adults (18–21) who engaged in a telemedicine visit between March 15, 2021 and December 31, 2022 at two pediatric primary care clinics whose patients are predominantly insured by Medicaid. A qualitative descriptive design was used to develop a taxonomy. Frequencies were obtained to identify the most prevalent themes. Results: Twenty-six participants (22 parents, 4 young adults) were interviewed. Twelve (46%) participants were English-speaking and 14 (53%) were Spanish-speaking. Four domains were identified, each further classified into themes: pre-visit expectations (option for in-person visit, general anticipation, and specific worries), visit experience (general sentiment, technology, and quality of care), comfort (with overall process, privacy, and communication), and feelings about telemedicine (advantages, disadvantages, and loss of telemedicine). Although many participants had negative expectations of telemedicine prior to their appointment, a majority indicated positive experiences with visits and concerns about a possible future where telemedicine visits at home were no longer covered by their health insurance. Discussion: Most participants indicated positive experiences with telemedicine and perceived negative impact if access was removed. Findings related to perceived quality of care, advantages, and disadvantages suggest that patient preferences and individual circumstances should be taken into account when choosing visit modality in similar settings.